Selection of Fuel System for Modern Heavy Duty Diesel Engines - G. M. Kukharonok; O. S. Rukteshel; M. U. Putsejeu (Наука и техника)
Fuel systems of diesel engines have been analyzed. The paper shows components of the systems, peculiarities of their manufacturing process. Difference in efficiency of the systems, their application and market prospects are considered in the paper. While solving problems to design a power installation the essence of fuel system selection is given on the basis of an internal combustion engine.